RISET EVALUASI - Nina Arifa; Nuril Huda; Dina Hermina (CV. ADIBA AISHA AMIRA, 2025)
Evaluation research is a research method used to assess the effectiveness, efficiency and impact of a particular programme, policy or intervention. Quantitative research in evaluation research focuses on the collection and analysis of numerical data to provide objective results on programme success. The research process includes setting evaluation objectives, developing hypotheses, research design, collecting data, analysing statistics and interpreting results. Commonly used data collection methods include surveys, tests, structured observations and secondary data. Results from quantitative evaluation research provide valuable input for programme improvement and evidence-based decision-making.